Język młodych tarnowian w świetle korespondencji elektronicznej - Małgorzata Kuruc (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2010)
The article presents the results of research on the vocabulary used in e-mails by young inhabitants of Tarnów. The research corpus consists of about 200 e-mails written by pupils of Tarnów schools between March 2007 and April 2008. Main emphasis of the research is put on the novel linguistic forms which determine the innovative character of e-mail communication, in particular: technical and technological vocabulary, abbreviations and acronyms, borrowings, graphic signs and specific spelling forms, and vulgarity of expression. Those observations do not characterize the whole lexicon, but only a selected fragment of the linguistic reality, yet on this basis we may claim that the internet language of the youth is strongly influential and growing in range, and should become a subject of a detailed linguistic analysis.